The Use of Portfolio to Assess Students’ Learning Autonomy in Enhancing Their Writing Skill: The Case of MA Madarijul Huda - Mawiliana, Putri (Universitas Negeri Semarang, 2021)
Abstract___________________________________________________________________This study aims to analyze and explain self- assessment, peer- assessment, and teacher-student conference implementation to enhance the students’ writing skills and explore the effect of the portfolio to explain the development of students' learning autonomy. The subject consisted of the eleventh-grade students of Islamic Senior High School Madarijul Huda in Pati regency, Central Java, Indonesia. Observation, interview, document analysis, and questionnaire were used to collect the data. This study found that the three assessment activities in the portfolio could enhance the students' writing skills. First, the self-assessment reflected the students' learning progress. They were honest in correcting the text and confident in completing the task. Second, the peer- assessment allowed the students to get the new academic experiences from their friends. Besides, the students were encouraged to keep the friendship well, more tolerant, and talkative. Third, the group's teacher-student conference inspired the students to build good teamwork, but passive members hindered the cooperation. Some members sometimes relied on the teacher's explanation. The students had an excellent ability to manage collaboration. Some conclusions can be drawn as follows: a) some high achieving students claimed they were autonomous learner before applying portfolio; b) the self- assessment activity could develop the students’ learning autonomy; c) students categorized as pro-active learners could play as leaders, problem solvers, and negotiators in the classroom